Recent progress in exosomal non-coding RNAs research related to idiopathic pulmonary fibrosis - Yajing Wei; Mingyang Hong; Huiming Zhu; Feng Li (Frontiers in Genetics)
Idiopathic Pulmonary Fibrosis (IPF) is a progressive interstitial lung disease characterized by unknown etiology and limited therapeutic options. Recent studies implicate exosomal non-coding RNAs (ncRNAs) as crucial regulators in IPF. These ncRNAs, including long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs), are involved in cellular processes through various mechanisms of selective packaging, intercellular communication, and signaling pathway integration. LncRNAs such as LINC00470 and PVT1 exhibit pro-fibrotic effects, while others like lnc-DC and THRIL show inhibitory roles; some, including UCA1 and MALAT1, demonstrate bidirectional regulation. In miRNAs, pro-fibrotic agents (e.g., miR-486, miR-223) contrast with inhibitory miRNAs (e.g., miR-34a, miR-126), while miR-21 and miR-155 display dual functions. Similarly, circRNAs such as circ_0000479 and circ_0026344 promote fibrosis, whereas circ_0000072 and circ_0000410 act as inhibitors, with certain circRNAs (e.g., circ_002178 and circ_0001246) exhibiting complex regulatory effects. Exosomal ncRNAs modulate key pathways, including TGF-β and Wnt/β-catenin, influencing IPF progression. Despite their potential, challenges remain in exosome isolation, functional characterization of ncRNAs, and clinical translation. Addressing these barriers through innovative research strategies is essential to leverage exosomal ncRNAs in the management and treatment of IPF. This review comprehensively examines the roles of exosomal ncRNAs in IPF, elucidates their mechanisms and pathway interactions, and discusses future perspectives to enhance understanding and therapeutic strategies for this disease.